The CYP3A4*1B allele increases risk for small cell lung cancer: effect of gender and smoking dose - Dally, Heike; Edler, Lutz; Jäger, Birgit; Schmezer, Peter; Spiegelhalder, Bertold; Dienemann, Hendrik; Drings, Peter; Schulz, Volker; Kayser, Klaus; Bartsch, Helmut; Risch, Angela (Pharmacogenetics and genomics, 2003)
CYP3A isozymes are involved in tobacco carcinogen- and steroid-metabolism, and are expressed in human lung tissue showing interindividual variation in expression and activity. The CYP3A4*1B allele has been associated with a two-fold higher promoter activity and with high-grade prostate cancers. The very frequent intron 3 polymorphism in the CYP3A5 gene (CYP3A5*3) results in decreased CYP3A5 protein levels. A case-control study was conducted in 801 Caucasian lung cancer patients that included 330 adenocarcinomas, 260 squamous cell carcinomas, 171 small cell lung cancers (SCLC) and 432 Caucasian hospital-based controls. CYP3A-genotyping was performed by capillary polymerase chain reaction followed by fluorescence-based melting curve analysis. A significantly increased SCLC risk for CYP3A4*1B allele carriers [odds ratio (OR) 2.25, 95% confidence interval (CI) 1.11-4.55, P = 0.02] was found. After dividing cases and controls by gender, an increased lung cancer risk for CYP3A4*1B carriers (OR 3.04, 95% CI 0.94-9.90, P = 0.06) for women but not for men (OR 1.00, 95% CI 0.56-1.81) was revealed. Heavier smoking men (≥ 20 pack-years) with the CYP3A4*1B allele had a significant OR for lung cancer of 3.42 (95% CI 1.65-7.14, P = 0.001) compared to *1A/*1A carriers with lower tobacco exposure (< 20 pack-years). For women, the respective OR was 8.00 (95% CI 2.12-30.30, P = 0.005). Genotype frequencies were generally in Hardy-Weinberg equilibrium, except for CYP3A5 where a greater than expected number of CYP3A5*1 homozygotes was observed among cases (P = 0.006). In addition, we observed linkage disequilibrium of CYP3A4 and CYP3A5 (P< 0.00001), but a non-significantly increased lung cancer risk was only found for homozygous CYP3A5*1 allele carriers (OR 5.24, 95% CI 0.85-102.28, P = 0.14) but not for heterozygotes. To confirm our observation that the CYP3A4*1B allele increases SCLC risk and modifies the smoking-related lung cancer risk in a gender-specific manner, further studies, including CYP3A haplotype analysis, will be necessary.
Im Titel ist [ast] als Sternchen dargestellt
Gesehen am 14.12.2020